Dissipation of fomesafen in fumigated, anaerobic soil disinfestation‐treated, and organic‐amended soil in Florida tomato production systems. Issue 2 (27th August 2019) - Li, Zhuona; Di Gioia, Francesco; Hwang, Jeong‐In; Hong, Jason; Ozores‐Hampton, Monica; Zhao, Xin; Pisani, Cristina; Rosskopf, Erin; Wilson, Patrick Christopher
Abstract: BACKGROUND: Fumigated, anaerobic soil disinfestation‐treated (ASD), and organic‐amended soil management strategies have been investigated as potential methyl bromide (MBr) alternatives for controlling diseases, nematodes, and weeds in soil. Nutsedge and broadleaf weed control using fomesafen has been reported to be comparable to MBr in normal cropping systems. There is no information on the fate of fomesafen used in combination with alternative practices. In this study, the fate of fomesafen in these alternative systems was measured by liquid chromatography‐tandem mass spectrometry (LC/MS–MS) following extraction using a modified Quick Easy Cheap Effective Safe (QuEChERS) method. RESULTS: The reported half‐life (DT50 ) values for fomesafen in the top 15 cm of soil were from 62.9 to 107.3 days. The DT50 values in organic‐amended soil were higher than in ASD‐treated soil in the top 15 cm. For all treatments, reductions in concentrations were positively correlated with lower redox potentials and organic matter content. Some leaching of fomesafen into the 16–30 cm zone was observed in all treatments. CONCLUSIONS: The DT50 values in this study were generally higher than those reported in previous studies performed at different locations. Due to increased losses of the herbicide and subsequent reduction in weed control, fomesafen is likely not to be suitable for effective weed control in systems using ASD techniques employing composted poultry litter and molasses. Integration of fomesafen using composted yard waste 1 (CYW1) and Soil Symphony Amendment (SSA) may result in acceptable weed control. Given that the soil was very sandy and the pH was higher than the p K a, fomesafen might leach deeper than 30 cm, particularly with the use of chemical soil fumigants (CSFs). © 2019 Society of Chemical Industry Abstract : Fomesafen dissipated more quickly in the ASD treatment using composted poultry litter + molasses, causing inadequate weed control, while dissipation was reduced in SSA, CYW1 and CSF treatments, with acceptable weed control results.